-12=2(2-x)

Simple and best practice solution for -12=2(2-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12=2(2-x) equation:


Simplifying
-12 = 2(2 + -1x)
-12 = (2 * 2 + -1x * 2)
-12 = (4 + -2x)

Solving
-12 = 4 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-12 + 2x = 4 + -2x + 2x

Combine like terms: -2x + 2x = 0
-12 + 2x = 4 + 0
-12 + 2x = 4

Add '12' to each side of the equation.
-12 + 12 + 2x = 4 + 12

Combine like terms: -12 + 12 = 0
0 + 2x = 4 + 12
2x = 4 + 12

Combine like terms: 4 + 12 = 16
2x = 16

Divide each side by '2'.
x = 8

Simplifying
x = 8

See similar equations:

| U^4-u^2+36=0 | | -8(3v-5)=23-7v | | -21=n-1 | | b+-2=0 | | 2/3x12= | | 11x=4-2 | | 3x^2+6x+3=18 | | Ax+bx=dx | | -19/16=a/16 | | -1+4x+x-2=12 | | -84=7x | | .2(x+3)-4(2x-3)=-3 | | 128=8(-2x+6) | | 0.5+3.6=4.2-1.5t | | 0.48-0.18x=0.45x-3.3 | | k/13=3 | | -2=x-7-6x | | 6(4x+6)+4(6x+6)+3=48x+64 | | 40+8v=6(1+7v) | | 2y-7=-19 | | .2(x+3)-4(2x-3)=3 | | 7m-4=-9+2m | | x+6=2x-14+11 | | 32x^8y^12/4x^2y | | 15x+14=4(23x+3) | | -6+12k=-90 | | 2x^2-5=-205 | | 1/3(9x) | | M-4/3-5m-9/7=3 | | 7k+8-k=6 | | -8/9z=32/45 | | -8r+2r=12 |

Equations solver categories